(untitled) (Bangladesh Journal of Medical Science, 2026)
The COVID-19 pandemic has dramatically changed the lives of people around the world. Millions of patients have experienced the infection in various forms, from mild symptoms to extremely severe conditions. Over time, it became clear that some patients, even after the acute phase, experience various sequelae that can lead to persistent changes in the body and a reduced quality of life. This prolonged course of the disease has been termed “long COVID” or “post-COVID syndrome” (PCS). It is known that the largest number of hospitalizations and deaths worldwide associated with the novel coronavirus infection occur among the elderly. Atypical clinical presentations, polymorbidity, polypharmacy, and the presence of geriatric syndromes occupy a special place in the care of geriatric patients. Metabolic syndrome (MS) is characterized by the simultaneous presence of obesity, hypertension, dyslipidemia, and hyperglycemia, which leads to an increased risk of cardiovascular disease. MS affects nearly 35% of the adult population in the United States, and its prevalence increases with age. BJMS, Vol. 25 No. 01 January’26 Page : 243-252